Penerapan Statistical Quality control dan Root Cause Analysis dalam Analisis Defect PDI Painting PT XYZ - Cahyani, Widia Aulia; Arsiwi, Pramudi (Metode : Jurnal Teknik Industri, 2026)
Abstract Painting quality control (PDI Painting) at PT XYZ plays an important role in ensuring the final quality of products. The purpose of this study is to identify the most common types of defects and their causes in the Painting process. The research was conducted over two months using direct observation, interviews, and documentation, and analyzed using Statistical Quality control (SQC) and Root Cause Analysis (RCA) methods, including Checksheets, Pareto diagrams, fishbone diagrams, and the 5 Whys technique. The results showed that the most dominant defect was pinholes (18.43%), followed by thin paint, uneven paint, and overspray. The main contributing factors included a lack of operator skills, uneven paint mixing, and unstable spray pressure. The recommendations provided were regular operator training, the use of paint thickness measuring tools, and an automatic paint mixing system to reduce the defect rate. Overall, this study confirmed that defects in the PDI Painting stage had a significant impact on production efficiency and rework costs. By integrating the SQC method to identify defect patterns and RCA to trace the root causes, an understanding of the factors affecting quality was obtained. The practical implications of this study are the need to improve operator competence, standardize work methods, and ensure consistent machine maintenance. By implementing the proposed improvements, PT XYZ has the potential to reduce the number of defects by 20–30% and improve product quality consistency.